Small-Cell Neuroendocrine Carcinoma of the Cervix Masquerading as a Cervical Fibroid: Report of a rare entity - Mukta Pujani; Kanika Singh; Varsha Chauhan; Raina Chawla; Rashmi Ahuja (Sultan Qaboos University Medical Journal, 2018)
Primary neuroendocrine tumours of the cervix are extremely rare, with an incidence of only 0.5–1%; as such, these entities can present a clinical and diagnostic challenge. Small-cell neuroendocrine carcinomas of the cervix are highly aggressive tumours that have a tendency to metastasise. We report a 44-year-old woman who presented to the Gynaecology Clinic of the Employees State Insurance Corporation Medical College & Hospital, Faridabad, India, in 2016 with menorrhagia. Based on a clinical examination, she was provisionally diagnosed with a cervical fibroid. However, a biopsy revealed features of a small-cell neuroendocrine carcinoma of the cervix which was subsequently confirmed via immunohistochemistry. An accurate diagnosis of a neuroendocrine carcinoma is vital as it forms the basis for treatment decisions as well as informing predictions for long-term survival.